Factors associated with 12 week case-fatality in Staphylococcus aureus bacteraemia: a prospective cohort study. (November 2016) - Braquet, P.; Alla, F.; Cornu, C.; Goehringer, F.; Piroth, L.; Chirouze, C.; Revest, M.; Lechiche, C.; Duval, X.; Le Moing, V.
Abstract: Staphylococcus aureus bacteraemia (SAB) is a frequent and deadly disease. Given the lack of a randomized trial, optimal first-line antibiotic treatment is still debated. Our aim was to identify prognostic factors in SAB patients and to analyse the impact of first-line antibiotics. The VIRSTA prospective cohort study was conducted in eight tertiary care centres in France. Consecutive incident adults in whom a blood culture drawn in participating centres grew S. aureus between April 2009 and October 2011 were prospectively followed for 12 weeks. Factors associated with 12-week case-fatality were identified by multivariate logistic regression. We enrolled 2091 patients and analysed survival in 1972 (median age 67.8 years, interquartile range 55.5–78.9; females 692/1972, 35.1%). SAB was nosocomial or healthcare-related in 1372/1972 (69.6%) of cases and the primary focus was unknown in 414/1972 (21.0%) of cases. Week 12 case-fatality rate was 671/1972 (34.0%). The main independent prognostic factors on multivariate analysis were age (adjusted OR by 10-year increment 1.56; 95% CI 1.44–1.69), septic shock (OR 5.11; 95% CI 3.84–6.80), metastatic cancer (OR 4.28; 95% CI 2.88–6.38), and unknown primary focus (OR 2.62; 95% CI 2.02–3.41). In the 1538 patients with methicillin-sensitive S. aureus (MSSA) bacteraemia, first-line empiric antistaphylococcal penicillins (OR 0.40; 95% CI 0.17–0.95) and vancomycin (OR 0.37; 95% CI 0.17–0.83), alone or combined with an aminoglycoside, were associated with better outcome compared with other antibiotics. There are few modifiable prognostic factors for SAB. Initiating empiric antibiotics with antistaphylococcal penicillins or vancomycin may be associated with better outcome in MSSA bacteraemia.